Anarkisme dan Sensualisme Televisi Indonesia - Nur Hamzah (Raheema, 2015)
Nowadays, television could not be separated from sophisticated people. Furthermore, for the most of people, television is an accompanying. Meanwhile, it is used as a source of information and entertainment for others. The modern people evenly depend on television. However, television does not merely afford the enjoyment and educative values, it also possesses the dark sides and negative effects. Based on Cultivation Theory, people who watch television intensely more than 4 hours tend to construct the aired program as a reality. It is similar to Indonesian television businesses, due to the number of advertisements, not all programs could be watched. For instance, Ganteng-ganteng Srigala, 7 Manusia Harimau, Naruto and so forth, contain the negative values, such as anarchism, vandalism, and sensuality. Eventually, if the adults do not undertake the strengthening effort to filter the negative programs, the audiences perhaps will fall to the negative values of television.